1986
DOI: 10.1111/j.1600-0528.1986.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges in lymphocytes of dentists and chairside assistants: no indication of a mutagenic effect of exposure to waste nitrous oxide

Abstract: Cytogenetic methods are used increasingly for monitoring occupational exposure to potential mutagenic agents. By one such method, the sister chromatid exchange (SCE) test, previous studies of hospital operating room personnel did not indicate any mutagenic effect from exposure to waste anesthetic gases. Dentists and their assistants are exposed to much higher levels of nitrous oxide than hospital personnel, and in studies of dentists it is possible to eliminate bias from concomitant exposure to halogenated ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, there is little clinical evidence of genotoxicity after occupational exposure to nitrous oxide as a sole agent. 127 More recent studies have focused on mixed anesthetic gas exposure, demonstrating an association between occupational exposure and markers of genotoxicity (sister chromatid exchange, DNA strand breaks, and micronuclei formation) in lymphocytes. 128,129 In a study of 50 physicians (25 anesthesiologists and 25 unexposed controls), occupational exposure to sevoflurane (8.9 Ϯ 5.6 ppm) and nitrous oxide (119 Ϯ 39 ppm) was associated with increased levels of sister chromatid exchange.…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is little clinical evidence of genotoxicity after occupational exposure to nitrous oxide as a sole agent. 127 More recent studies have focused on mixed anesthetic gas exposure, demonstrating an association between occupational exposure and markers of genotoxicity (sister chromatid exchange, DNA strand breaks, and micronuclei formation) in lymphocytes. 128,129 In a study of 50 physicians (25 anesthesiologists and 25 unexposed controls), occupational exposure to sevoflurane (8.9 Ϯ 5.6 ppm) and nitrous oxide (119 Ϯ 39 ppm) was associated with increased levels of sister chromatid exchange.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Although the levels exceeded OELs in this study, an earlier study showed a similar effect of occupational exposure to nitrous oxide and isoflurane even when the levels were below the OELs. 127 Therefore, there is a little evidence to suggest that occupational exposure to nitrous oxide alone induces genotoxic effects; however, when anesthesiologists are exposed to mixed gases (nitrous oxide plus a volatile anesthetic), genotoxic effects are apparent. Again, longitudinal cohort studies, with quantified gas exposure, are required to assess the impact of this occupational exposure on the health of anesthesiology staff.…”
Section: Genotoxicitymentioning
confidence: 99%